2013
DOI: 10.1001/2013.jamaneurol.286
|View full text |Cite
|
Sign up to set email alerts
|

Posterior Cingulate Glucose Metabolism, Hippocampal Glucose Metabolism, and Hippocampal Volume in Cognitively Normal, Late-Middle-Aged Persons at 3 Levels of Genetic Risk for Alzheimer Disease

Abstract: To characterize and compare measurements of the posterior cingulate glucose metabolism, the hippocampal glucose metabolism, and hippocampal volume so as to distinguish cognitively normal, late-middleaged persons with 2, 1, or 0 copies of the apolipoprotein E (APOE) ε4 allele, reflecting 3 levels of risk for lateonset Alzheimer disease.Design: Cross-sectional comparison of measurements of cerebral glucose metabolism using 18 F-fluorodeoxyglucose positron emission tomography and measurements of brain volume usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
112
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(123 citation statements)
references
References 44 publications
(83 reference statements)
3
112
1
Order By: Relevance
“…The prodromal stage encompasses the presymptomatic and mild cognitive impairment stages of AD. White line = progression of cognitive decline through the 5 stages of AD [11][12][13][14][15][16][17]. FDG-PET = fluoro-2-deoxyglucose positron emission tomography; MRI, magnetic resonance imaging adenosine triphosphate (ATP) production [9].…”
Section: Current Strategies Targeting Mitochondria and Bioenergetics mentioning
confidence: 99%
See 1 more Smart Citation
“…The prodromal stage encompasses the presymptomatic and mild cognitive impairment stages of AD. White line = progression of cognitive decline through the 5 stages of AD [11][12][13][14][15][16][17]. FDG-PET = fluoro-2-deoxyglucose positron emission tomography; MRI, magnetic resonance imaging adenosine triphosphate (ATP) production [9].…”
Section: Current Strategies Targeting Mitochondria and Bioenergetics mentioning
confidence: 99%
“…Decrements observed in cerebral glucose metabolism using fluoro-2-deoxyglucose positron emission tomography (FDG-PET) and brain volume using magnetic resonance imaging are early signs of bioenergetic decline in the prodromal state of AD ( Fig. 1) [16]. Observations from a clinical trial of the Dominantly Inherited Alzheimer's Network suggested several surrogate disease markers, including compromised FDG-PET signal in specific brain regions (posterior cingulate cortex and prefrontal cortex) vulnerable to development of AD pathology, that arise in patients with AD decades before cognitive symptoms [11-15, 17, 24, 44].…”
Section: Current Strategies Targeting Mitochondria and Bioenergetics mentioning
confidence: 99%
“…3, using the florbetapir (18F-FDG) positron emission tomography (PET) imaging technique, it has been shown that the APOE alleles in chromosome 19 and butyrylcholinesterase (BCHE) can be regarded as Aβ peptide deposition regulator [47]. In cognitively normal AD patients, the cortex glucose metabolism rate (CMRgI) is significantly reduced for Apo-E ε4 carrier [ε4 +], especially in the front frontal lobe, parietal lobe, temporal lobe and posterior cingulate regions [48][49][50][51][52]. Apo-E ε4 dose is related with higher and earlier risk of dementia [50].…”
Section: Pet Mri Dti and Fmri Imaging For Apo-e ε4 And Their Influementioning
confidence: 99%
“…109 Glucose hypometabolism has been associated with the presence of the APOE e4 allele in non-demented older adults. [110][111][112] In the FDG-PET study by Reiman et al, 95 the sample of cognitively normal middle-aged and elderly individuals was subdivided into APOE e4 homozygous (n=24), heterozygous (n=38), and non-carriers (n=55). In some cortical regions, the relationship between hypometabolism and CVRFs had greater salience in e4 allele carriers than in non-carriers.…”
Section: Cardiovascular Risk Factors and Cognitive Declinementioning
confidence: 99%
“…On the other hand, findings involving the lateral temporoparietal neocortices lost their significance when the analysis was repeated after controlling for the effects of the e4 allele, 113 indicating that metabolism in those latter regions may be influenced by APOE, as suggested by previous PET studies of non-elderly subjects. 95,114,115 Although e4-related hypometabolism has been associated with the neuropathological processes of AD, 112,116 such findings may not be necessarily pathological or specifically linked to AD. 117 For instance, APOE e4 is also a risk factor for vascular disease.…”
Section: Cardiovascular Risk Factors and Cognitive Declinementioning
confidence: 99%